Use and meaning teachers assign to the integration of the MICA 3.0 kit for teaching climate change - Pino, Sonia; Cofre, César; Vergara, Humberto; Vergara, Luis; Solís-Pinilla, Jaime; Arenas-Martija, Andoni; Ampuero, Paulina; Merino, Cristian (Frontiers in Education, 2025)
IntroductionTeaching climate change requires teachers to have the educational resources that will facilitate teaching this content and visualize how a global problem has various local implications. In Chile, the capacity for environmental data collection and use at the school level remains limited, hindering evidence-based and context-aware climate education.MethodsThis study follows a Design-Based Research (DBR) approach and comprises three main phases: (1) the participatory design of an environmental monitoring station based on the needs identified by in-service teachers for teaching climate change; (2) the development and implementation of a professional development course to support teachers in the appropriation of the technological resource; and (3) the analysis of learning experiences designed by teachers who integrated the technology into their pedagogical practices.ResultsTeachers successfully designed active learning experiences that incorporated local environmental data. These experiences promoted the development of scientific skills and 21st-century competencies, contextualized within local territories and cultures, with the potential of opening new spaces for learning beyond the classroom.DiscussionThe integration of the monitoring station transformed teachers’ views of technology, shifting from an instrumental perspective to one linked to key scientific inquiry processes. It also supported the design of active and contextualized learning experiences that promote scientific and 21st-century skills. The relevance and low cost of the resource make it a viable option for scaling, although challenges remain in teacher training related to basic statistics and environmental data management.